A SURVEY OF POTENT FOLKLORE MEDICINAL PLANT USED BY ETHNIC PEOPLE OF THUTHIPATTU AND KARUVATCHI VILLAGE, VILLUPURAM DISTRICT OF TAMIL NADU, INDIA (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The present study was carried out in two geographically isolated Hillocks, Sacred Groves and Unclassified Vegetation of Gingee Taluk of Villupuram district, Tamil Nadu, India, a region inhabited by farmers and tribal groups. Data obtained through guided field-walk method on ethnomedicinal plants and ethnographic profile of respondents was documented using semi structured questionnaires. Information on medicinal plants with their correct botanical identities with family, local names, parts used, is carefully recorded. It resulted in about 50 medicinal plants used for the treatment of several diseases either in single or in combination with some other ingredients. The survey shows that the informants in two villages have very good knowledge about the medicinal plants used for various ailments. This present study analyzed the data collected from the study area by applying the quantitative ethnobotanical devices such as, Use value (UVi), Factor informant consensus (Fic) and Fidelity level (F1%).